AN ANALYSIS OF SENTENCE STYLE IN â€œTHE RIDDLEâ€ BY WALTER DE LA MARE - Prasetyo, Dwi (JURNAL LITERARY CRITICISM, 2019)
This analysis aims to describe sentence style in the short story "The Riddle" by Walter de la Mare. The data in this analysis is the word, phrases, clauses, sentences and paragraphs contained in the short story "The Riddle" by Walter de la Mare. Technique data collection in this analysis is reading techniques and note-taking techniques. This analysis is done by identifying, describing, and analyze sentence styles in the short story The Riddle by Walter de la Mare based on stylistic and parallelism reviews and the context of grammatical use of sentences. The results of this analysis are about the description of the points in the review. On the effect aspects of using the sentence style in The Riddle short stories by Walter de la Mare. The description is how sentence by sentence in a paragraph produces or creates an effect or indicates a happy effect, feeling sorry or pity, feeling angry or irritated, feeling sad or touched. From that all we can find out how the writer of The Riddle short story, Walter de la Mare, raises an effect on the sentence he uses in the story.   Keywords: short story, stylistics, parallelism, sentence style, analysis